1990
DOI: 10.1111/j.1939-165x.1990.tb00535.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Hematology and Serum Chemistry Values in the Beagle Dog

Abstract: To distinguish age-related changes in hematology and clinical chemistry values from those resulting from disease, hematology, and clinical chemistry values of healthy, age-matched Beagle dogs 3 to 14 years of age were analyzed. Serum potassium, total protein and globulin concentration, and lactic dehydrogenase activity increased with age, while urea nitrogen, creatinine and albumin concentration, and gamma-glutamyl transferase activity decreased. The 12-year-old group had some distinct differences from the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
50
1
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 4 publications
13
50
1
2
Order By: Relevance
“…This is a new finding, as in most published studies only beagle dogs were used (James & Heywood 1979, Lowseth et al 1990 or differences in body and thus testes size were ignored (Taha & Noakes 1982). Our finding is in accordance with those of a study in which no relation was found between the size of the animal and testosterone concentrations in 10 different species (Wichmann et al 1984).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is a new finding, as in most published studies only beagle dogs were used (James & Heywood 1979, Lowseth et al 1990 or differences in body and thus testes size were ignored (Taha & Noakes 1982). Our finding is in accordance with those of a study in which no relation was found between the size of the animal and testosterone concentrations in 10 different species (Wichmann et al 1984).…”
Section: Discussionsupporting
confidence: 82%
“…Either no reduction with age (Taha & Noakes 1982, Lowseth et al 1990 or decreasing testosterone concentrations has been reported (Bondarenko et al 1979, Günzel Apel et al 1990; in accordance with the latter observation, lower LH concentrations were observed in aged dogs also (Günzel Apel et al 1990).…”
Section: Introductionsupporting
confidence: 72%
“…But also, there is a suggestion that brain pathology, including the age of onset and extent may vary across breeds (Bobik et al 1994). In laboratory beagles, the median lifespan (i.e., 50% have died) can be as high as 12-14 years depending on the colony evaluated (Lowseth et al 1990;Albert et al 1994). Of note, there are examples of "exceptional longevity" in pet/companion dogs (Cooley et al 2003) consistent with increasing numbers of "oldest-old" human in our aging population (Head et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Urea was increased in 14-year-old dogs. 43 Last, a lifetime study of laboratory Beagles from the Center for Environmental Toxicology and Technology at Colorado State University reported autopsy findings for 276 control dogs, 95% of which were >10 years of age. In this cohort, chronic azotemic renal disease was the cause of death in 22 control dogs (8%).…”
Section: Clinicopathologic Changes In Aged Dogsmentioning
confidence: 99%